If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -9)(x + 1) + 8x = 0 Reorder the terms: (-9 + x)(x + 1) + 8x = 0 Reorder the terms: (-9 + x)(1 + x) + 8x = 0 Multiply (-9 + x) * (1 + x) (-9(1 + x) + x(1 + x)) + 8x = 0 ((1 * -9 + x * -9) + x(1 + x)) + 8x = 0 ((-9 + -9x) + x(1 + x)) + 8x = 0 (-9 + -9x + (1 * x + x * x)) + 8x = 0 (-9 + -9x + (1x + x2)) + 8x = 0 Combine like terms: -9x + 1x = -8x (-9 + -8x + x2) + 8x = 0 Reorder the terms: -9 + -8x + 8x + x2 = 0 Combine like terms: -8x + 8x = 0 -9 + 0 + x2 = 0 -9 + x2 = 0 Solving -9 + x2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + x2 = 0 + 9 Combine like terms: -9 + 9 = 0 0 + x2 = 0 + 9 x2 = 0 + 9 Combine like terms: 0 + 9 = 9 x2 = 9 Simplifying x2 = 9 Take the square root of each side: x = {-3, 3}
| 3(x-5)+6(3-x)=5x-13w | | 8+5=213 | | -15=-n+6n | | 2y=8-9x | | 6x^3+30x^2+7x+35=0 | | 75+2x=180 | | -2x-10+4x+25=-2 | | x=-20+3X | | 2(4f+2g)2=8f+2g | | -5x+8+7x=6 | | 2(4f+2g)2=2f(4+2g) | | 3=3tx-5x | | cos(x)+cos(3x)=2sen(6x)cos(x) | | -4=-2(8x-12) | | 3=3t*-5x | | cos(x)+cos(3x)= | | Y-14=4(x-2) | | b=(3.14)(12)2 | | 5x*5x-15x-50=0 | | s*5-22=98 | | 5w-11=89 | | 9x-2=5x+8 | | 5x-10xy=5(x-2y) | | 5x-4=10y | | 2x+9=5x+54 | | 2x+15=x+16 | | 5/9+2/9= | | -6-2(m+4)=36 | | 3y-11=2y-6 | | 4x-5(2x+1)=7x+3(4x-5) | | 3/2-2/7= | | x+x+x+2=3+2x |